The Role of Empathy, Self-Control, Self-Compassion, and School Climate in Madrasah Students for Predicting Cyberbullying in Yogyakarta - Muniratul Husna; Partino Partino; Abd. Madjid; Fitriah M. Suud (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of empathy, self-control, school climate, and self-compassion on cyberbullying in Islamic schools. This study uses a quantitative methodology, using a questionnaire that measures cyberbullying, empathy, self-control, school climate, and self-compassion. The population in this study consisted of 1,314 students, with a sample of 605 students drawn from two schools. The sampling technique was simple random sampling, and the analysis used LISREL SEM. The results show that empathy, self-control, school climate, and self-compassion influence cyberbullying. Empathy hurts cyberbullying. Self-control hurts cyberbullying. School climate hurts cyberbullying. Self-compassion hurts cyberbullying. This study shows that more people need to be aware of the dangers of cyberbullying. This research also has implications for starting intervention programs, school rules, and more research on how empathy, self-control, school climate, and self-compassion can help prevent students from becoming victims of cyberbullying. This study suggests that empathy, self-control, self-compassion, and a favorable school climate can be protective factors against cyberbullying among madrasah students. These findings imply the need to develop intervention programs and school policies that support strengthening these aspects to prevent cyberbullying.